Acupuncture reversed hippocampal mitochondrial dysfunction in vascular dementia rats. (January 2016) - Li, Hui; Liu, Yi; Lin, Li-Ting; Wang, Xue-Rui; Du, Si-Qi; Yan, Chao-Qun; He, Tian; Yang, Jing-Wen; Liu, Cun-Zhi
Abstract: Hippocampal mitochondrial dysfunction due to oxidative stress has been considered to play a major role in the pathogenesis of vascular dementia (VD). Previous studies suggested that acupuncture could improve cerebral hypoperfusion-induced cognitive impairments. However, whether hippocampal mitochondria are associated with this cognitive improvement remains unclear. In this study, an animal model of VD was established via bilateral common carotid arteries occlusion (BCCAO) to investigate the alterations of cognitive ability and hippocampal mitochondrial function. BCCAO rats showed impairments in hippocampal mitochondrial function, overproduction of reactive oxygen species (ROS) and learning and memory deficits. After two-week acupuncture treatment, BCCAO-induced spatial learning and memory impairments as shown in Morris water maze were ameliorated. Hippocampal mitochondrial respiratory complex enzymes (complex I, II, IV) activities and cytochrome c oxidase IV expression significantly increased, which might contribute to the reduction of hippocampal ROS generation. In addition, acupuncture significantly improve mitochondrial bioenergy parameters such as mitochondrial respiratory control rate and membrane potential not PDH A1 expression. Placebo-acupuncture did not produce similar therapeutic effects. These findings suggested that acupuncture reversed BCCAO-induced hippocampal mitochondrial dysfunction, which might contribute to its prevention on cognitive deficits. Highlights: Hippocampal mitochondrial dysfunction is involved in the pathogenesis of VD. The function of hippocampal mitochondria and cognitive ability are reduced in BCCAO rats. Acupuncture reduces ROS generation and reversed mitochondrial dysfunction in BCCAO rats. The reversion of hippocampal mitochondrial dysfunction contributes to cognitive improvement.